Peluang Kerja Sama Internasional dalam Relokasi Ibu Kota Baru Indonesia - Mujiono, Dadang Ilham Kurniawan; Sagena, Uni Wahyuni (Department of International Relations, Universitas Mulawarman, 2020)
Relocation plan of the new capital city of Indonesia is the agenda of every president of Indonesia. However, only in President Joko Widodo, the plan to relocate the capital started implementing seriously. Such as decided East Kalimantan province as the location of the new capital city, creation of timeline projects and conducted design competition of the new capital city. This research paper focuses on the discussion of opportunities for international cooperation in the project of the new capital city of Indonesia. The type of research is a predictive descriptive which describes the plan for transferring of the new capital city and predicts international cooperation that will occur based on the exposure of news during the transfer project began to be implemented. Then, the data used is secondary data derived from the journal, presentation documents and reliable news of both print and electronic media. The results of this study show that the international cooperation opportunities in the new capital city's project are enormous, and actors are involved not only from the state but multi actors